Mechanism underlying the acceleration of pitting corrosion of B30 copper–nickel alloy by Pseudomonas aeruginosa - Li, Huan; Sun, Mingxian; Du, Min; Zheng, Zhenxu; Ma, Li (Frontiers in Microbiology, 2023)
Despite its excellent corrosion resistance, B30 copper–nickel alloy is prone to pitting, particularly when exposed to microorganisms. The mechanism underlying the acceleration of pitting in this alloy is not fully understood. In this study, the acceleration of pitting corrosion in B30 copper–nickel alloy caused by a marine microorganism named Pseudomonas aeruginosa (P. aeruginosa) was investigated using surface analysis and electrochemical techniques. P. aeruginosa significantly accelerated the pitting in B30 copper–nickel alloy, with a maximum pitting depth of 1.9 times that of the abiotic control and a significant increase in pitting density. This can be attributed to extracellular electron transfer and copper–ammonia complex production by P. aeruginosa, accelerating the breakdown of the passivation film.